EARLY DETECTION OF ADOLESCENT MENTAL HEALTH DURING THE COVID-19 PANDEMIC AT SMA NEGERI 1 PEMATANG RAYA SIMALUNGUN REGENCY - Daulay, Wardiyah; Damanik, Einjel Tiyo Marlina (Indonesian Journal of Medical Anthropology, 2022)
The Covid-19 pandemic has caused the Indonesian government to issue a PSBB (Large-Scale Social Restriction) policy. The implementation of this policy has the risk of causing mental health disorders in adolescents, especially middle teens who like to be in groups with their peers. Therefore, early detection of adolescent mental health during the Covid-19 pandemic needs to be done to prevent and deal with disorders that can occur in adolescent growth and development. This study aims to identify the mental health of adolescents during the Covid-19 pandemic at SMA Negeri 1 Pematang Raya, Simalungun Regency. The population of this study were all students of SMA Negeri 1 Pematang Raya, totaling 1024 with a total sample of 288 people. The sample was determined by simple random sampling technique. The research instrument used was a modified Strength and Dificulties Questionnaire (SDQ). The results of this study indicate that in the weakness domain which consists of 4 subdomains namely emotional problems, behavior problems, hyperactivity, and relationship problems with peers, as many as 124 adolescents (43.1%) are at risk for experiencing relationship problems with peers during the pandemic.